Exopolysaccharides Play a Role in the Swarming of the Benthic Bacterium Pseudoalteromonas sp. SM9913 - Liu, Ang; Mi, Zi-Hao; Zheng, Xiao-Yu; Yu, Yang; Su, Hai-Nan; Chen, Xiu-Lan; Xie, Bin-Bin; Zhou, Bai-Cheng; Zhang, Yu-Zhong; Qin, Qi-Long (Frontiers in Microbiology, 2016)
Most marine bacteria secrete exopolysaccharide (EPS), which is important for bacterial survival in the marine environment. However, it is still unclear whether the self-secreted EPS is involved in marine bacterial motility. Here we studied the role of EPS in the lateral flagella-driven swarming motility of benthic bacterium Pseudoalteromonas sp. SM9913 (SM9913) by a comparison of wild SM9913 and ΔepsT, an EPS synthesis defective mutant. Reduction of EPS production in ΔepsT did not affect the growth rate or the swimming motility, but significantly decreased the swarming motility on a swarming plate, suggesting that the EPS may play a role in SM9913 swarming. However, the expression and assembly of lateral flagella in ΔepsT were not affected. Instead, ΔepsT had a different swarming behavior from wild SM9913. The swarming of ΔepsT did not have an obvious rapid swarming period, and its rate became much lower than that of wild SM9913 after 35 h incubation. An addition of surfactin or SM9913 EPS on the surface of the swarming plate could rescue the swarming level. These results indicate that the self-secreted EPS is required for the swarming of SM9913. This study widens our understanding of the function of the EPS of benthic bacteria.